Hubungan Smarthphone Addiction dan Tingkat Stres Terhadap Kejadian Insomnia pada Remaja di SMA Negeri 8 Banda Aceh - Diara Anjelia; Syukriadi Syukriadi; Nurul Sakdah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The prevalence of insomnia in Indonesia is still high compared to other countries, especially in adolescents. The prevalence is about 67% including low insomnia at 55, 8% and moderate insomnia at 23, 3%. The impact of insomnia on adolescents such as body weakness, lethargy, lack of concentration, and enthusiasm until it becomes a serious problem such as sleep disorders, heart attack, cancer, obesity, and other various lethal diseases. This study aimed to determine the correlation between smartphone addiction and stress levels on the incidence of insomnia in adolescents at SMA Negeri 8 Banda Aceh. The research method used was an analytical design with a cross-sectional approach. The population was 537 teenagers and the sample was 84, chosen using the Proportional Random Sampling technique and Univariate and bivariate analysis using the Chi-Square test. The data were gathered using the Perceived Stress Scale (PSS) questionnaire, Smartphone Addiction Scale Short Version (SAS-SV), and Biological Psychiatry Study Group Jakarta Insomnia Rating Scale (KSPBJ-IRS). The result showed that of 84 respondents, most of them did not experience insomnia 41 respondents (48,8%), did not experience smartphone addiction 43 respondents (51,2%), and experienced low stress 48 respondents (57,1%). So there was a relationship between smartphone addiction (p=0,002) and stress level (p=0,007) toward insomnia in adolescents. In conclusion, there was a correlation between smartphone addiction and stress levels toward the incidence of insomnia in adolescents. This research suggests that research institutes concerned with health education conduct cross-sector collaboration regarding smartphone usage, such as the Health Office and Public Health Centres.